RETRACTED: Tax procedural proof: problems of theory and practice - I. V. Glazunova; D. S. Sheptunov (Правоприменение, 2022)
RETRACTED ARTICLEThe subject of this study is the legal norms contained in legislation, other legal acts, as well as materials of law enforcement practice that determine the specifics of tax procedural evidence. This article also analyzes the experience of legal regulation of the mechanism of tax procedural evidence, examines the gaps in tax legislation directly related to the topic under consideration.The purpose of the study is to identify and analyze the features of evidence in the tax process, to study the application of evidence theory in the activities of tax authorities, to develop new ways, means and simplified procedures for effective proof, as well as to prepare appropriate regulatory changes. The objectives of the study are to identify and analyze the advantages and disadvantages of the current state of the regulatory regulation of the means and procedures of tax procedural proof; to study the distribution of the duty of proof from the position of the presumptions proclaimed in tax legislation, the established grounds for exemption from proof, as well as the blocks of circumstances formed by law enforcement practice that are subject to proof, respectively, by the tax authority and a participant in the tax process controlled by it; formulation of the author 's position on the general rule of burden of proof distribution and proposals for adaptation in the Tax Code of the Russian Federation constructions of grounds for exemption from proof according to the presented concept; allocation of stages of evidentiary activity carried out within the framework of the tax process.Methodology. Within the framework of this article, general scientific methods were applied in the framework of comparative, logical and statistical research and analysis of law enforcement and judicial practice in the field of tax process.The main results. Within the framework of the study, a number of issues related to the chosen topic were considered. First of all, it is necessary to understand that by proving in the tax process, one should consider the procedural activities of authorized participants in the tax process for collecting, researching and evaluating evidence, ensuring the adoption of legitimate and justified procedural decisions on issues that are subject to the regulation of tax legislation. The general subject of proof in the tax process is the circumstances relevant to the decision of the tax authority in the cases provided for by the legislation on taxes and fees, determined by the tax authority based on the substance of the relationship and the positions of its participants in accordance with the applicable rules of substantive law in cases where such circumstances are not defined by the legislation on taxes and fees. For the general the rule for distributing the burden of tax procedural proof is to adopt the following judgment: "Each participant in the relationship regulated by the legislation on taxes and fees, in order to comprehensively and most fully establish the facts relevant to the decision of the tax authority in the cases provided for by the legislation on taxes and fees, must prove the circumstances to which he refers as the basis of his procedural position (claims, objections)."Conclusions. The interests of the state in replenishing the budget should not lead to violations of the rights of an unlimited number of taxpayers. To do this, it is necessary to apply the norms on the presumption of innocence and increased standards for proving an offense committed by a taxpayer in tax disputes. The imposition by the tax authorities of their approach to regulating tax legal relations is going beyond the powers of the tax authorities. The application in practice of the presumption of taxpayers' guilt in committing a tax offense, which is not provided for by law, violates not only the private interests of taxpayers, but also represents an encroachment on public interests, on public order, since obvious injustice is being done.